UTILIZATION OF INSTAGRAM IN SHAPING ADOLESCENT LIFESTYLES: A CASE STUDY OF SMPN 9 KOTA TEBING TINGGI - Meika Ananda Priskarini; Muhammad Alfikri (Program Pascasarjana UIN Sumatera Utara, 2026)
The development of social media has changed the communication and social interaction patterns of adolescents, especially through visual platforms such as Instagram, which allow users to express themselves, build self-image, and gain social recognition from their circle of friends. Instagram not only functions as a medium for entertainment, but also as a digital communication space that influences how adolescents shape their identity and lifestyle. This study uses a qualitative approach with a case study method conducted on grade IX-1 students of SMP Negeri 9 Kota Tebing Tinggi. Research informants were selected through a purposive sampling technique with the criteria of students actively using Instagram. Data collection was carried out through observation, structured interviews, and documentation of students' Instagram usage activities. Data analysis was conducted using the Miles and Huberman interactive model, which includes data reduction, data presentation, and drawing conclusions. The research findings show that Instagram is used by adolescents as a means of social interaction, following trends, and displaying self-identity through uploading photos, videos, and the story feature. Responses in the form of likes and comments also influence self-confidence and how adolescents view themselves in the digital social space. In addition, Instagram use also contributes to shaping adolescents' views on lifestyle, such as how to dress, social activities, and the tendency to follow trends on social media. However, face-to-face communication in the school environment still has an important role in building social relationships between students and in the process of forming adolescent personalities.